Informal education for management in health tourism - Bakić, Ognjen (Array, 2008)
Republic of Serbia recently adopted “Strategy of tourism development until 2015”, in which, among the other long-term goals, is indicated the urgent need of the development of human resources and long term education for the needs of prospective and faster tourism development. Both are considered, improvement of formal, as well as informal education which are under the strong influence of Bologna process, that the republic of Serbia joined. It is necessary to understand the fact that in the first domain a longer time range of adjustment from the point of organization contents will be necessary, as long as the results, and that in the second domain the results can be expected much faster. Bearing that in mind, the Ministry of Tourism in the year 2006 and 2007 from the NIP funds (National Investment Plan), separated the certain amount of finance and assigned them to a larger number of educational programs (Seminars) which are realized by relevant high education and other institutions. This article is dedicated to the educational seminar which, under the name of „Management in the Health Tourism“, was realized by Faculty for Business in Services from Sremska Kamenica in cooperation with HMS (Hotel Management Solutions), from Belgrade, with the intention of sharing our experience as the professors who led, organized and participated in the above mentioned seminar, with our colleagues who will take part in 19th Biennial International Congress (Tourism and Hospitality in 2008), and with the aim of collecting suggestions and recommendations for our further activity, since this will be our duty on the continuous base